Elbow joint variability during the round off in female gymnastics - Farana, R.; Uchytil, J.; Jandacka, D.; Zahradnik, D.; Irwin, G. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Based on a within-gymnast analyses this study aimed to examine the variability in elbow joint kinematics and kinetics of expert gymnasts in the execution of the round-off with different hand position. Six international level female gymnasts performed 10 trials of the round-off from a hurdle step to back handspring with "parallel" and "T-shape" hand position. Two force plates were used to determine ground reaction forces. Eight infrared cameras were employed to collect the kinematic data. Gymnast-specific variability was calculated using coefficient of variation (CV%) in each discrete kinematic and kinetic measures. In conclusion higher variability in the elbow joint abduction angle and adduction moment of force in the T-shaped hand position may leads to reducing repetitive abduction stress and thus protect elbow joint from overload.